ИННОВАЦИОННАЯ ДЕЯТЕЛЬНОСТЬ И ЕЕ ВЛИЯНИЕ НА СИСТЕМУ БУХГАЛТЕРСКОГО УЧЕТА: ЕВРОПЕЙСКИЙ И НАЦИОНАЛЬНЫЙ АСПЕКТ - Golocialova, Irina (CEP USM, 2017)
In conditions universal innovation economy is becoming innovation-driven economies. To that effect may still need to be formed innovative system. To State has an important role to play in the organization of this process. This comes through development and implementation of institutional platform. In the financial reporting are presented results activities of every company including innovative company. The objective of financial reporting is to provide transparency information of users in making economic decisions. Because accordance concept of transparency requires developing specify mechanism of accounting in the implementation of the innovative activities. In this research are looking indentified of problems.
Keywords: innovation; innovative activities; institutional platform; mechanism of accounting